FACTORS CONTRIBUTING TO DEMOCRATIC CULTURE ALERTNESS: A CASE STUDY OF SUAN SUNANDHA RAJABHAT UNIVERSITY (BACHELOR DEGREE STUDENTS) - Sangkhachat, Kanyakorn; Jaidee, Khanthong; Sarananthawat, Kanphet (PEOPLE: International Journal of Social Sciences, 2020)
The objectives of the research are: 1) to study the level of attentiveness in democratic culture; 2) to compare the level of attentiveness in democratic culture based upon personal factors and political socialization; and 3) to study factors contributing to the attentiveness in democratic culture. The samples are 181 bachelor students studying Political Science at the College of Innovation and Management. The research used surveys for data collection. Statistical analysis was done using frequency, percentage, mean, standard deviation, t-test, One-way ANOVA and Multiple Regression Analysis. The research found; 1) the students’ level of attentiveness to democratic culture is at the highest 2) hypothesis testing found student’s major is a factor contributed to difference in democratic culture attentiveness while gender, age, religion and college year do not contributed to difference in democratic culture attentiveness; and 3) Multiple Regression Analysis shown political socialization, family institution, educational institution, and peer factors have effect on employee engagement at 35.3 percent.